El Epitaphium Leandri, Isidori et Florentinae (ICERV 272) o la compleja transmisión manuscrita de un texto epigráfico: nueva edición y estudio - Martín-Iglesias, José Carlos 1968- (2010)
This article presents the first critical edition of the Epitaphium Leandri, Isidori et Florentinae (ICERV 272) based on all extant manuscripts and a complete study of the textual tradition. It is supplemented with notes on metrical and linguistic issues.
Keywords: Crítica textual; Epigrafía; Transmisión de textos; Manuscritos